The role of organizations in caring for the mental health of people with disabilities - جاف, د. مروان مظهر; سليمان, نيان عزيز; Ahmed, Dr. Jaafar Omar; Abdullah, Muzaffar Jabbar (Sulaimani Journal for Humanities, 2026)
People with disabilities are an important section of any society, with their own abilities and ideas. They do not belong to any group, religion or nation, but are part of the whole structure of societies. In the new world, providing their rights, behavior and non-discrimination between different sections of society, including people with disabilities, is considered one of the hallmarks of developed societies. All international declarations and treaties emphasize the elimination of discrimination among different communities and sections of society. People with disabilities deserve recognition and non-discrimination. In the Kurdistan Region, despite the existence of laws on the rights and privileges of people with disabilities, discrimination and attitudes towards them are still discussed. Building an inclusive society is one of the goals of any developed society in which all sections of society participate side by side without discrimination. The achievement of this goal (the inclusive society) is not the sole responsibility of one party or group in society. In this regard, civil society organizations, especially organizations advocating for people with disabilities, play an important role. In this regard, the researchers of the research (The role of organizations in mental health care of people with disabilities - a field study in Halabja disabled organization based on the radical theory method) work based on the latest scientific methods In order to highlight the most important role of civil society organizations, especially (Halabja Disabled Organization) to provide mental health of people with disabilities.